High Prevalence of Hepatitis Delta Virus among Patients with Chronic Hepatitis B Virus Infection and HIV-1 in an Intermediate Hepatitis B Virus Endemic Region. (January 2014) - Saravanan, Shanmugam; Madhavan, Vidya; Velu, Vijayakumar; Murugavel, Kailapuri G.; Waldrop, Greer; Solomon, Sunil S.; Balakrishnan, Pachamuthu; Kumarasamy, Nagalingeswaran; Smith, Davey M.; Mayer, Kenneth H.; Solomon, Suniti; Thyagarajan, Sadras P.
We conducted a study to investigate HIV and hepatitis delta virus (HDV) coinfection among patients with chronic hepatitis B virus (HBV) infection and the triple infection's (HIV/HBV/HDV) clinical implications in India, an intermediate HBV endemic region, with an estimated HIV-positive population of 2.5 million. A total of 450 patients (men: 270; women: 180) with chronic HBV infections and 135 healthy volunteers were screened for HIV and HDV. The incidence of the triple infection was low (4 [0.8%]) compared with dual infections of HIV-1/HBV (7 [1.5%]) and HBV/HDV (22[4.8%]). Among 21- to 40-year-olds, HBV/HDV coinfection (45.8%) and HBV/HDV/HIV-1 triple infection was predominant (75%). Among 11 patients coinfected with HIV-1/HBV, 4 (36%) were tri-infected and were also associated with chronic hepatitis and cirrhosis. The HDV coinfection was higher among patients coinfected with HBV/HIV-1, despite the declining trend in HDV infection among HIV-negative patients, as previously reported. Thus, it is important to assess the impact of HIV, chronic HBV, and HDV tri-infection in India.